Strategic Management / Awareness and Change: Third Edition - Thompson John L (International Thomson Business Press, 1997)
The book has a fresh, attractive and clear page design, and includes learning objectives, mini-cases, boxed examples, key terms, summaries, checklists for revision, further reading, questions and research assignments. Preface, Acknowledgements, Strategic Management, Exploring Strategic Management, A Business Management Framework, Strategic Leadership and Decision Making, Culture and Values, Strategic Awareness, The Organizational Mission and Objectives, Strategic Success: How Are We Going?, Company Failure, Environmental and Resource Analysis: Synergy, The Business Environment, The Competitive Environment and Competitive Advantage, The Content of Competitive Strategies, Competitive Advantage Through Products and Processes and Service, Competitive Advantage Through People, Financial Strategy, Competitive Advantage and Information, The Content of Corporate Strategy, Planning and Creating Corporate Strategy, Strategic Alternatives and Market Entry Strategies, Issues in Strategic Growth, Issues in Strategic Consolidation and Recovery, Strategy Evaluation and Choice, Strategy Implementation and Change and Control, Corporate strategy and Corporate Management Style, Issues in Strategic Change Management.